2017
DOI: 10.1213/ane.0000000000001885
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Forced Vital Capacity to Predict Low Lung Compliance and Select Intraoperative Tidal Volume During Thoracic Surgery

Abstract: FVC is more strongly correlated to TLC than PBW and a cutoff of about 3.5 L can be utilized to predict low pulmonary compliance. The equation Vt = FVC/8 reduced mean calculated tidal volume in patients with low pulmonary compliance and/or small lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In this regard, as residual volume increases, FVC declines in commensurate fashion. In turn reduced FVC in severe asthma may also reflect reduced lung compliance [ 2 ]. Air trapping and airway remodelling are hallmarks of small airways dysfunction (SAD) in severe asthma [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, as residual volume increases, FVC declines in commensurate fashion. In turn reduced FVC in severe asthma may also reflect reduced lung compliance [ 2 ]. Air trapping and airway remodelling are hallmarks of small airways dysfunction (SAD) in severe asthma [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between actual lung capacity and PBW based on patient's height was not strong (R = 0.58-0.65), and was especially poor in patents with low lung compliance (Fig. 4) [37]. If PBW does not reflect patients' actual lung size reliably, and patients have different 'functional lung size' due to underlying lung pathologies, applying fixed V T based on PBW would frequently result in alveolar over-distension or atelectasis.…”
Section: T Titrationmentioning
confidence: 96%
“…Lung capacity is not well correlated with predicted body weight (PBW). Adapted from Hoftman et al [37]. (12 vs. 11 days, P = 0.04) and ICU stays (5 vs. 4 days, P = 0.01) were shorter in open lung approach with no difference in in-hospital mortality (n = 320) [47].…”
Section: Alveolar Recruitmentmentioning
confidence: 96%
“…Our group studied the relationship between predicted body weight and total lung capacity in thoracic surgery patients, utilizing both traditional data from pulmonary function tests and novel computed tomography-based image processing. 9 Using the Vitrea software package (V6.4, Vital Images, USA), we generated each patient's three-dimensional lung image and calculated the precise volume of air contained at end inspiration. Surprisingly, we found that lung volumes in patients with similar predicted body weight varied by as much as 100%, raising serious concerns about relying on predicted body weight formulas alone to select protective tidal volumes in these patients.…”
Section: Ventilation and Complications After Lung Resection: Commentmentioning
confidence: 99%
“…Their work did not report on clinical outcomes. 3 As these authors acknowledge, their data were derived from a small retrospective dataset, and their results are exploratory. Large clinical trials should be conducted before revising clinical care pathways.…”
Section: In Replymentioning
confidence: 99%